Carta del Presidente William H. Taft a Roberto H. Todd - Todd, Roberto H.; Taft, William H. (My University, 1912)
Carta relacionada epístola de agradecimiento.
Keywords: White House (Washignton, D.C.); Taft, William H.--Correspondence.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.